Method for screening pertussis toxin-specific small molecule inhibitors - Nieminen, Ilona (My University, 2026)
Whooping cough is a highly contagious respiratory disease caused by the bacterium Bordetella pertussis. Whooping cough is especially dangerous for infants and young children who have not developed immunity to the disease and have the highest risk for severe outcomes. The major virulence factor of B. pertussis is pertussis toxin (Ptx) which is AB5-type exotoxin consisting of S1 – S5 subunits. S1 subunit catalyzes the adenosine diphosphate (ADP) -ribosylation reaction in which the ADP-ribose is transferred from β-nicotinamide adenine dinucleotide (β-NAD+) to a C-terminal cysteine residue on the inhibitory α-subunit of G protein. ADP-ribosylation makes G protein-coupled receptors non-functional, disturbing the signaling pathway, which causes the pathochemistry of B. pertussis. Effective vaccination strategies have reduced the number of diagnosed whooping cough cases globally, but the effectiveness of vaccines has decreased in recent years. In addition, antibiotic resistance has reduced the effectiveness of antibiotic treatment, which has been the main treatment strategy for years. Moreover, antibiotics that are used to treat whooping cough are generally nonspecific, leading to a decrease in microbial flora in the gut. Therefore, more selective drugs are needed to enable effective and safe treatment strategies for the whooping cough in the future. Small molecules have been considered as a potential drug candidate for the treatment of whooping cough, but the lack of effective small molecule screening approaches have limited the research. Label-free screening techniques, like thermal stability assay (TSA) is often utilized as a label-free screening method. It is based on the heat denaturation of protein, which reveals hydrophobic aromatic residues. Intrinsic TSA readout can be performed by monitoring tryptophan (Trp) fluorescence, which fluorescence intensity increases upon protein denaturation. Steady-state fluorescence spectroscopy is another label-free approach which monitors changes in fluorescence intensity over time. However, it requires that the aromatic residues whose fluorescence is monitored are at the correct position in the protein structure. Steady-state fluorescence spectroscopy provides kinetic information on small molecule binding to the protein, compared to the TSA which offers information about protein-ligand interactions through protein stability changes. However, protein-ligand ratio is often unfavorable in both methods, due to their relative low sensitivity, and thus, additional techniques are needed. In the thesis, the first kinetic Trp fluorescence-based small molecule screening method for Ptx was developed. Developed method allow the kinetic study of β-NAD+ hydrolysis activity with small molecules. S1 subunit of Ptx was utilized in the screening as its structure contains only one Trp residue in the catalytically active site which fluorescence intensity is monitored over time. Decrease in Trp fluorescence was observed upon β-NAD+ binding to the active site due to the β-NAD+ stacking interaction with Trp, causing quenching of its fluorescence. As hydrolysis proceeded, Trp fluorescence increased because β-NAD+ was degraded to ADP-ribose and nicotinamide. Multiple small molecules from different analog groups were successfully studied using the developed method even though the changes in association and hydrolysis activity of Ptx were small. The results obtained with the developed method can be used to design more effective inhibitors, and the method is a good starting point for other intrinsic fluorescence based screening approaches. The method is also excellently suited for studying the β-NAD+ hydrolysis activity of mutated Ptx proteins and is unique in this respect.

Hinkuyskä on Bordetella pertussis bakteerin aiheuttama herkästi tarttuva hengityselinsairaus. Hinkuyskä on erityisen vaarallinen imeväisille ja pienille lapsille, joille ei ole kehittynyt immuniteettia tautia vastaan ja joilla on suurin riski saada vakava tautimuoto. B. pertussiksen tärkein virulenssitekijä on pertussistoksiini (Ptx), joka on AB5-tyyppinen eksotoksiini koostuen S1 – S5 alayksiköistä. S1 alayksikkö katalysoi adenosiinidifosfaatti (ADP) -ribosylaatioreaktiota, jossa ADP-riboosi siirretään β-nikotiiniamidiadeniinidinukleotidiltä (β-NAD+) C-terminaaliseen kysteiiniin G-proteiinin inhiboivassa α-alayksikössä. ADP-ribosylaatio aiheuttaa toimintahäiriöitä G-proteiinikytkentäisiin reseptoreihin johtaen solusignaloinnin häiriöihin ja kliinisiin oireisiin. Tehokkaat rokotusstrategiat ovat vähentäneet diagnosoitujen hinkuyskätapauksien määrää maailmanlaajuisesti, mutta rokotteiden teho on heikentynyt viime vuosina. Myös lisääntynyt antibioottiresistenssi on heikentänyt antibioottihoidon tehokkuutta, joka on ollut keskeisin hinkuyskän hoitokeino. Hinkuyskän hoitoon käytetyt antibiootit ovat myös epäspesifisiä ja siten heikentävät suoliston mikrobiomia. Tämän vuoksi tarvitaan selektiivisempiä lääkkeitä varmistamaan tehokas ja turvallinen hinkuyskän hoito tulevaisuudessa. Pienmolekyylejä on pidetty potentiaalisina lääkeainekandidaatteina hinkuyskän hoidossa, mutta tehokkaiden pienmolekyyliseulontamenetelmien puute on rajoittanut tutkimusta. Leima-vapaita seulontatekniikoita, kuten lämpöstabiiliusmääritystä (TSA), käytetään usein leima-vapaana seulontamenetelmänä. TSA perustuu proteiinin lämpödenaturaatioon, mikä paljastaa hydrofobiset aromaattiset aminohapot. Luontainen TSA signaali voidaan mitata seuraamalla tryptofaanin (Trp) fluoresenssia, jonka intensiteetti kasvaa proteiinin denaturoituessa. Stationääritilan fluoresenssispektroskopia on toinen leima-vapaa lähestymistapa, jossa seurataan fluoresenssi-intensiteetin muutoksia ajan funktiona. Se kuitenkin edellyttää, että aromaattiset aminohapot, joiden fluoresenssia seurataan, ovat oikeassa paikassa proteiinin rakenteessa. Stationääritilan fluoresenssispektroskopia antaa kineettistä tietoa pienmolekyylin sitoutumisesta proteiiniin, verrattuna TSA:han, joka tarjoaa tietoa proteiinin ja ligandin välisistä vuorovaikutuksista proteiinien stabiilisuusmuutosten kautta. Proteiini-ligand-suhde on kuitenkin molemmissa menetelmissä usein epäedullinen alhaisen herkkyyden vuoksi, ja tämän vuoksi tarvitaan uusia menetelmiä. Opinnäytetyössä kehitettiin ensimmäinen kineettinen Trp:n fluoresenssiin perustuva pienimolekyyliseulontamenetelmä Ptx:lle. Kehitetty menetelmä mahdollistaa β-NAD+:n hydrolyysiaktiivisuuden kineettisen tutkimuksen pienmolekyyleillä. Seulonnassa hyödynnettiin Ptx:n S1-alayksikköä, koska sen rakenne sisältää vain yhden Trp:n aktiivisessa keskuksessa, jonka fluoresenssin voimakkuutta seurataan ajan funktiona. Trp:n fluoresenssin havaittiin pienenevän β-NAD+:n sitoutuessa aktiiviseen keskukseen sen pinoutumisvuorovaikutuksien seurauksena. Hydrolyysin edetessä Trp:n fluoresenssi kasvoi, koska β-NAD+ hajotettiin ADP-riboosiksi ja nikotiiniamidiksi. Menetelmällä seulottiin onnistuneesti useita molekyylejä eri analogiryhmistä, vaikka muutokset assosiaatio- ja hydrolyysiaktiivisuuksissa olivat pieniä. Menetelmällä saatuja tuloksia voidaan käyttää tehokkaampien inhibiittorien suunnittelussa, ja menetelmä toimii hyvänä lähtökohtana muille luontaista fluoresenssia hyödyntäville menetelmille. Menetelmä soveltuu erinomaisesti myös mutatoitujen Ptx proteiinien β-NAD+-hydrolyysiaktiivisuuden tutkimiseen ja on siinä ainoa laatuaan.
Keywords: ADP-ribosylation; drug development; pertussis toxin; tryptophan fluorescence; small molecule inhibitor; screening method; method development; ADP-ribosylaatio; lääkekehitys; pertussistoksiini; tryptofaanifluoresenssi; pienmolekyyli-inhibiittori; seulontamenetelmä; menetelmäkehitys